Tapping new opportunities in personal mobility market: opportunities & challenges for SUZUKI Bangladesh - Rana, Masud (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.